International Symposium on Radiative Transfer - da Silva, Carlos B. (2009)
The interaction between turbulence and radiation (TRI) is a relevant issue in turbulent reactive flows, yielding a significant increase of the radiative heat fluxes in comparison with laminar flows [1, 2]. However, our knowledge about such interaction is still limited. Direct numerical simulation (DNS) provides fundamental and reliable insight on turbulent flows, but it can only be applied to simple geometries and low Reynolds number flows, because of the high computational requirements. Recently, DNS has been used to investigate TRI in simple premixed and diffusion combustion systems [3, 4]. Furthemore, we have reported statistical data of the radiation intensity field a homogeneous isotropic turbulent non-reactive flow using a pseudo-spectral code for the DNS, and a ray tracing method along with a statistical narrow band model for the radiative transfer calculations [5]. However, some features of the radiative calculations reported in [5] were not fully consistent with the requirements of the flow simulation, such as the definition of the boundary conditions, and the dependence of the statistical data on the number of samples was not investigated. These drawbacks are eliminated in the present work.